Avaluation of center of gravity of children and adolescents with Mucopolysacaridosis type VI (Research, Society and Development, 2021)
Introduction: Mucopolysaccharidosis type VI (MPS VI) or Maroteaux-Lamy syndrome is a rare, hereditary metabolic disease, known as a lysosomal deposit disease where patients have progressive deformities. There is a need to understand how the center of gravity (CG) of these patients behaves, as a way of preventing falls and directing therapy. Objective: To evaluate the projection of the center of gravity in a static way for children and adolescents with MPS VI through the postural assessment software (SAPO®). Methodology: This is a descriptive, cross-sectional study, carried out in a reference center for rare diseases, with patients with MPS VI. The evaluation was performed in a static way through analysis using SAPO®. Results: 15 volunteers were evaluated, 60% (9) were male, with an average age of 7.80 ± 3.66. Asymmetries were found in the frontal and sagittal planes, with a greater asymmetry in the sagittal plane: 34.68% ± 18.04 asymmetry, with a maximum value of 73.7%. The CG of 93.9% of those evaluated were anteriorized. Conclusion: Based on the reports issued by SAPO®, it can be said that there are changes in the CG of children and adolescents with MPS VI.